A new gender equality model based on Qur’ānic perspective - Ahmad, Nadzrah; Othman, Roslina; Aminudin, Rabi'ah; Ghazali, Norzulaili (IIUM Press, International Islamic University Malaysia, 2019)
The concept of gender equality often deemed as Western product and contradictory to Islamic approaches of understanding gender. As Islam plays crucial role in the Malaysian society as well as embedded as part of the state institution, there has been dilemmas of the government agency to meet the requirement of international conventions which based the principles of gender equality with the sameness in all aspects of life for both men and women that at times contradict with the Islamic perspectives of gender equality. This dilemma is further exacerbated with the misinterpretation of Qur’ānic verses on women which is imbued with cultural norms and values in regards to the role and position of women in society. The lack of understanding among Muslim countries on the concept of gender equality is also due to the absence of a comprehensive gender equality model compatible with Islam that can guide and frame state institutions in their decision-making in matters related to gender. This study is a qualitative research that employs to textual inductive method to analyses selective Qur’ānic verses that address women in both directive and non-directive manner to be the basis of the development of new gender equality model. This research aims to develop a new gender equality model based on Qur’ānic perspective. It addresses the misconception of gender issues in Muslim societies as well as offers an alternative model for state institutions in Muslim majority countries in managing gender related matters. This research contributes to the new understanding of gender equality especially for a Muslim majority country like Malaysia and enhance the Malaysian government’s efforts to empower Malaysian women and address gender issues as outlined in the National Women Policy, the Women’s Development Action Plan and the Millenium Development Goals under the purview of the Ministry of Women, Family and Community Development.